The Autobiography of Samuel Smiles, LL.D. - Smiles, Samuel 1812-1904 (Cambridge library collection. Technology, 1905)
One of the most popular Victorian writers, Samuel Smiles (1812–1904) made his name in 1859 with the original self-improvement manual Self-Help. His highly successful multi-volume Lives of the Engineers (also reissued in this series) contained biographies of men who had, like him, achieved greatness not through privilege but through hard work. Left incomplete at his death, edited by the social theorist Thomas Mackay (1849–1912) and first published in 1905, his autobiography opens with a vivid description of the Scottish garrison town of his birth during the Napoleonic wars. In his later years he was a vocal supporter of state education, and the value of education was a constant theme throughout his life. He remembers his schooldays here with clarity, writing that 'a good education is equivalent to a good fortune'. Straightforward and unpretentious, this book will be of interest to historians and readers fascinated by the Victorian drive for self-improvement